2020
DOI: 10.2337/db19-0984
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Stress Shapes CTL Immune Recognition of Preproinsulin Signal Peptide by Posttranscriptional Regulation of Endoplasmic Reticulum Aminopeptidase 1

Abstract: The signal peptide of preproinsulin is a major source for HLA class I autoantigen epitopes implicated in CTL-mediated beta-cell destruction in Type 1 Diabetes (T1D). Among them, the 10-mer epitope located at the C-terminal end of the signal peptide was found to be the most prevalent in recent onset T1D patients. While the combined action of signal peptide peptidase and endoplasmic reticulum aminopeptidase 1 (ERAP1) is required for processing of the signal peptide, the mechanisms controlling signal peptide trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…In a previous study, we found that mRNA for both MHC class I and II were increased in β cells from T1D donors compared to non-diabetic donors [31]. A recent study revealed that inflammation and ER stress impacted peptide presentation by MHC class I in human β cells [33]. Mechanisms of MHC class I peptide presentation could be further explored using SC-β cells.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study, we found that mRNA for both MHC class I and II were increased in β cells from T1D donors compared to non-diabetic donors [31]. A recent study revealed that inflammation and ER stress impacted peptide presentation by MHC class I in human β cells [33]. Mechanisms of MHC class I peptide presentation could be further explored using SC-β cells.…”
Section: Discussionmentioning
confidence: 93%
“…The unfolded protein response (UPR) that is triggered by ER stress has been implicated in beta cell apoptosis in both T1D and type 2 diabetes 15 17 . Significantly, ER stress was proposed to contribute not only directly but also indirectly to beta cell death in T1D owing its ability to increase the presentation of auto- and neoantigens, for example by affecting post-translational modifications 14 , 18 20 and antigen processing 21 . We speculated that Rnls mutation may affect the cellular response to ER stress and thereby diminish the stimulation of diabetogenic CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…All six encode ER-resident proteins, including ER stress markers HSP90B1, CRELD2, and HSPA5, whose expression we also found to be significantly increased in most mutants by qPCR. The other three genes were PDIA4, DPAGT1, and ERAP1, all of which have also been implicated in ER stress or the UPR (Ferrari and Söling, 1999;Heifetz et al, 1979;Thomaidou et al, 2020). On the other hand, GO terms of downregulated genes were related to the synthesis of proteoglycan, a major component of the ECM, suggesting that ER stress may lead to a deterioration of ECM quality and interfere with the columnar arrangement of the growth plate.…”
Section: ) Indicating That This Mutation May Potentially Results mentioning
confidence: 99%